2021
DOI: 10.1038/s41598-021-02151-z
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of gene expression throughout fruit development in chili pepper

Abstract: Gene expression is the primary molecular phenotype and can be estimated in specific organs or tissues at particular times. Here we analyzed genome-wide inheritance of gene expression in fruits of chili pepper (Capsicum annuum L.) in reciprocal crosses between a domesticated and a wild accession, estimating this parameter during fruit development. We defined a general hierarchical schema to classify gene expression inheritance which can be employed for any quantitative trait. We found that inheritance of gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Indeed, our study revealed that a substantial portion of the transcripts that showed abundance differences between wild and domesticated plants display partially non-additive (dominant-recessive) gene action. This mode of gene action has been ignored in the majority of experiments assessing the inheritance of transcript accumulation in plants [1921, 24, 29, 4447]. Perhaps due to the use of discrete categories of modes of gene action based on differential expression between F0s and F1 hybrids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, our study revealed that a substantial portion of the transcripts that showed abundance differences between wild and domesticated plants display partially non-additive (dominant-recessive) gene action. This mode of gene action has been ignored in the majority of experiments assessing the inheritance of transcript accumulation in plants [1921, 24, 29, 4447]. Perhaps due to the use of discrete categories of modes of gene action based on differential expression between F0s and F1 hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…Which suggests a relevant role of transcript abundance variation in the modulation of domestication-related phenotypes. Indeed, several studies have reported that variation on transcript abundance of genes involved in organ size tends to show a recessive pattern of gene action for the domesticated phenotype [9, 10]. Transcript abundance is controlled by regulatory interactions between cis-acting non-coding DNA sequences and trans-acting factors such as transcription factors and chromatin remodeling factors [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That point is far away from the cross between the same parents in opposite direction, F 1 , which has its specialization close to the mean of that parameter and above the average ENL. The large differences in diversity and specialization between the two crosses, CQ and QC, as well as between them and the transcriptomes of their parents, QC and CM, are explained by the surprising heterogeneity in the inheritance of the gene expression patterns, which is discussed in [19].…”
Section: Analyses By Genotypementioning
confidence: 99%
“…The second factor was the fruit's development stage, which was sampled every ten days from anthesis to maturation in each one of the genotypes (see Materials and Methods). From the analysis of this experiment, we previously detected a set of genes relevant for the domestication process [18], unraveled the inheritance of gene expression patterns during fruit development in Capsicum [19], and developed a method to analyze time expression profiles [20][21][22]. Nevertheless, this experiment has not been previously analyzed with the tools derived from Shannon's Information Theory, as implemented in the R package "infoRNAseq".…”
Section: Introductionmentioning
confidence: 99%